PARAMETERS OF NUCLEAR MAGNETIC RESONANCE IN PATIENTS WITH CONGENITAL NARROWING OF THE LUMBAR SPINAL CANAL - MORALES-RANGEL,ELIU HAZAEL (2016)
ABSTRACT Objective: To compare the morphological parameters of magnetic resonance in patients with congenital narrowing of the lumbar spinal canal with patients with low back pain. Methods: A descriptive, retrospective, observational study was conducted with measurements in the axial and sagittal magnetic resonance sections of the vertebral body and canal of the lumbar spine of 64 patients with diagnosis of low back pain, which were compared with resonance images taken from 31 Mexican patients with congenital narrowing of the lumbar spinal canal. Results: The results show that patients with congenital narrowing of the lumbar spinal canal in the axial sections have a difference in diameters, being L2<13.9 mm, L3<13.3 mm, L4<12.9 mm, L5<13.1 mm, compared with controls L2<20.5 mm, L3<20.5 mm, L4<19.3 mm, L5<18.1 mm with p = 0.000. Conclusions: We found different measurements in the Mexican population compared to those found by similar studies. With the parameters obtained, it would be possible to make the proper diagnosis, surgical planning, and treatment.